Traetment Model Take and Give terhadap Retensi Siswa dalam Nama Istilah Biologi pada Materim Ekosistem di Madrasah Tsanawiyah Asas Islamiyah - Rizki Fitri Astuti (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, 2018)
The learning process at Madrasah Tsanawiyah Asas Islamiyah Sipin Kota Jambi still uses the learning model of teacher center learning so that the students do not understand the name of biology term especially their ecosystem material difficulties in memorizing and memories in their memory. Take and give model is a learning process that seeks to associate new knowledge with knowledge that has been owned by students. This research is a quantitative research using Posstest Only Control design design. The result of test data analysis of test